Finding value on a council estate: complex lives, motherhood, and exclusion - Mckenzie, Lisa Louise (2010)
This research focuses upon a group of women who are white and working class they live on the St Anns council estate in Nottingham and they are all mothers to mixed-race children. The focus of this study from the outset is to challenge the often negative and homogenous readings and namings of council estates in the UK and their residents. The problems that are within Britain's council estates are often complex and difficult to understand, therefore the research sets out to explain some of those complexities, whilst highlighting the disadvantages the women experience in their daily lives. The research explores the interaction between class, race and gender but also space, examining how poor neighbourhoods have become known in recent times as spaces of social exclusion and their residents have become known as 'the excluded'. The research explores how the women find value for themselves and their children when their social positions have been subject to stigma, and disrespect and their practices are misrecognised. Therefore the research examines the local value system and the local resources which are available and used by the residents of this council estate and asks in the absence of universal social and economic resources can people find value locally.